The used of Acrylonitrile-Butadiene Styrene- (ABS) pipe in cold water supply system / Muhammad Arif Abu Hassan - Abu Hassan, Muhammad Arif (Faculty of Architecture, Planning and Surveying, 2008)
The preparation of this dissertation was mainly motivated by the desire to provide an overview of The Used of Acrylonitrile Butadiene Styrene (ABS) Pipe in Cold Water Supply System especially at Immigration Department of Malaysia headquarters office, Putrajaya. The study has specific aim and objectives to achieve in the end. The primary aim study is about the water supply system in overall of the Department Of Immigration Malaysia Headquarters, Putrajaya by referring to the building plumbing schematic diagrams. A study on maintenance management system applied at Immigration Department of Malaysia headquarters, Putrajaya purposed to identify the types of water supply maintenance programs in the building. The problem occurs and effect using the ABS pressure pipe in cold water supply system for Immigration Department of Malaysia Headquarters, Putrajaya will be study to find and determine every cause of the problems and the way to solve it.